2016
DOI: 10.1186/s12878-016-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems and potential contributing factors in the management of deep vein thrombosis

Abstract: BackgroundPatients receiving anticoagulant drugs must be carefully screened for drug-related problems, as such medications, including warfarin have narrow therapeutic ranges and a high potential for complications. Thus, this study was designed to assess drug-related problems in the management of patients with deep vein thrombosis at Tikur Anbessa Specialized Hospital.MethodsA cross-sectional descriptive study involving retrospective chart review of adult patients with deep vein thrombosis was conducted from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Where detailed dose adjustment algorithms do not exist, clinicians may make erroneous or even paradoxical dose adjustments. Reviews from Cameroon, [8] Ethiopia, [9,14] and Namibia [19] report dose increases after 4%-17% of supratherapeutic INRs and dose decreases after 4%-15% of subtherapeutic INRs. In addition, dose adjustments are often inappropriately large: While clinical trial evidence has shown that warfarin dose adjustments of 10-15% were associated with better outcomes, [102] the mean warfarin dose increase in one Ethiopian review was 58% in response to an INR of 1.5 to 1.9 against a target of 2.0 to 3.0.…”
Section: {Table 3 Here}mentioning
confidence: 99%
See 1 more Smart Citation
“…Where detailed dose adjustment algorithms do not exist, clinicians may make erroneous or even paradoxical dose adjustments. Reviews from Cameroon, [8] Ethiopia, [9,14] and Namibia [19] report dose increases after 4%-17% of supratherapeutic INRs and dose decreases after 4%-15% of subtherapeutic INRs. In addition, dose adjustments are often inappropriately large: While clinical trial evidence has shown that warfarin dose adjustments of 10-15% were associated with better outcomes, [102] the mean warfarin dose increase in one Ethiopian review was 58% in response to an INR of 1.5 to 1.9 against a target of 2.0 to 3.0.…”
Section: {Table 3 Here}mentioning
confidence: 99%
“…In addition, dose adjustments are often inappropriately large: While clinical trial evidence has shown that warfarin dose adjustments of 10-15% were associated with better outcomes, [102] the mean warfarin dose increase in one Ethiopian review was 58% in response to an INR of 1.5 to 1.9 against a target of 2.0 to 3.0. [9] In the Namibian example, more than half of patients with an INR >4 were over-corrected so that their subsequent INR was subtherapeutic. [19] Warfarin formulations other than 5mg are frequently not available in SSA, [6,22] making precision dosing difficult.…”
Section: {Table 3 Here}mentioning
confidence: 99%
“…A similar result was found in Addis Ababa. 15 , 23 , 24 The highest incidence of DVT was varied from different studies. In most of the studies, DVT occurrence was high at a mean ± SD age of 63 ± 19.4 and 66 ± 17.…”
Section: Discussionmentioning
confidence: 99%
“…Where detailed dose adjustment algorithms do not exist, clinicians may make erroneous or even paradoxical dose adjustments. Reviews from Cameroon, 8 Ethiopia 9,14 and Namibia 19 report dose increases after 4‐17% of supratherapeutic INRs and dose decreases after 4‐15% of subtherapeutic INRs. In addition, dose adjustments are often inappropriately large: While clinical trial evidence has shown that warfarin dose adjustments of 10‐15% were associated with better outcomes, 103 the mean warfarin dose increase in one Ethiopian review was 58% in response to an INR of 1.5‐1.9 against a target of 2.0‐3.0 9 .…”
Section: Challenges With Dose Selection and Dose Adjustmentsmentioning
confidence: 99%
“…Reviews from Cameroon, 8 Ethiopia 9,14 and Namibia 19 report dose increases after 4‐17% of supratherapeutic INRs and dose decreases after 4‐15% of subtherapeutic INRs. In addition, dose adjustments are often inappropriately large: While clinical trial evidence has shown that warfarin dose adjustments of 10‐15% were associated with better outcomes, 103 the mean warfarin dose increase in one Ethiopian review was 58% in response to an INR of 1.5‐1.9 against a target of 2.0‐3.0 9 . In the Namibian example, more than half of patients with an INR >4 were over‐corrected so that their subsequent INR was subtherapeutic 19 …”
Section: Challenges With Dose Selection and Dose Adjustmentsmentioning
confidence: 99%